FLUORESCENT X-RAY IMAGING WITH PINHOLE CAMERA - Yu. I. Dudchik; G. I. Hilko; Yu. K. Lomashko (Приборы и методы измерений, 2016)
Pinhole camera is one of X-ray optics devices. The pinhole camera is used for obtaining the image of synchrotron and laboratory sources, and also as a lens in a method of X-ray fluorescent microscopy. This method allows to obtain information on a spatial distribution of various chemical elements to the areas of several square centimeters with spatial resolution at the level of 50–100 μm. As a rule energy-dispersive two-dimensional CCD cameras are used for imaging. Such cameras are expensive devices and have low sensitivity for X-rays with energy of photons higher than 8 keV. Therefore it is perspective to use for X-ray fluorescent microscopy more effective CCD cameras with a scintillator layer. The purpose of this work consists in development of the device for imaging with secondary fluorescent X-rays by using pinhole as a lens and CCD camera for registration of the X-ray image. The device for obtaining the image of objects in secondary X-rays is developed. The device consists of an X-ray tube, pinhole and CCD camera. The object of research was irradiated with radiation from the X-ray tube and emits secondary X-rays. 100-microns pinhole was used for formation of the image of the object at an entrance window of the CCD camera. Images of a number of the iron springs differing in the sizes are received. It is established that the spatial resolution of the device is about 200 μm at an exposition of 60 s. It is possible to improve permission of the device by increasing in an exposition, optimization imaging conditions and reduction of the pinhole size.